A pilot study exploring public awareness and knowledge of right hemisphere communication disorder compared with aphasia and stroke in Northwest London, UK. Issue 9 (1st September 2016) - Ivanszky, Zsofia; Cocks, Naomi; Dipper, Lucy
Abstract : Background : No previously published research has investigated public awareness and knowledge of Right Hemisphere Communication Disorders (RHCD). In comparison, there are a handful of published studies that have investigated public awareness and knowledge of aphasia. The results of these studies indicate that awareness and knowledge is low but has marginally increased in recent years, due to international efforts to raise the public profile of the disorder. Aims : The current study investigated public awareness and knowledge of RHCD and compared it to that of aphasia. Information regarding awareness and knowledge of stroke was also determined for those participants who did not have awareness of RHCD or aphasia. Methods & Procedures : A face-to-face survey of 87 members of the public was undertaken in North West London, United Kingdom. Outcomes and Results : Of the 87 survey respondents, only 9.2% reported having heard of RHCD and 4.6% met the criteria for having basic knowledge of this disorder. In comparison, 32.2% of participants had heard of aphasia and 24% had basic knowledge about it. While the results show that fewer people were aware and had knowledge of RHCD compared to aphasia, this difference was not significant. Of those participants who had heard of neither disorder, all had heard of and the majority had knowledge of stroke. Conclusions : The findings suggested that awareness of RHCD amongst members of the public is low. It is suggested that in order to improve quality of services, funding and social re-integration following a right hemisphere stroke, raising public awareness and knowledge is necessary.